The Challenges and Strategies of History Teachers in Utilizing Digital Learning Media: A Case Study at SMKN 1 Banjarmasin - Dimas Yoga Ferdiyanto; Cahyo Budi Utomo; Atno Atno (STKIP Taman Siswa Bima, 2025)
This study explores the implementation of digital media in transforming 21st-century history learning. The main problems identified include the limited optimal use of digital media in history lessons, the lack of learning models that align with local characteristics, and teachers’ challenges in adapting to technology, which are further exacerbated by technical constraints such as unstable internet connections in schools. Adopting a qualitative approach with a case study design, this research aims to analyze the use of digital media—such as videos, infographics, and interactive simulations—and its impact on student engagement. Data were collected through triangulation methods, including interviews, observations, documentation, and questionnaires, with data validity ensured through source triangulation and member checking. The findings reveal that the implementation of digital media by history teachers, applied in varied and integrated ways, has enhanced students’ enthusiasm and engagement. Students demonstrated greater focus when watching videos, showed excitement during discussions, and reported that lessons became more interesting, which increased their motivation to learn. Effective visualization helped students better understand complex concepts while fostering 21st-century skills, including collaboration, critical thinking, communication, and creativity, consistent with Constructivist Theory and the application of TPACK. This study recommends developing learning models tailored to local characteristics, improving infrastructure, and providing continuous teacher training to optimize the digitalization of history learning.